Decontamination of Water from Dissolved Pollutants by Special Ceramic (AKP1 & AKP2) - Abdulrazaq Jassim, Sanaa; ., . (International Journal of Engineering and Technology, 2018)
In this study, contaminated water was purified by ceramic purifieres produced from a mixture of Iraqi raw materials. These raw materials were activated kaolinite, Porcelanite, and Limestone. They were mixed with two different mixing pertcentages to produce two types of ceramic (AKP1 and AKP2). Ceramic filters were evaluated based on anumber of parameters that were: hydraulic conductivity, purified water properties, and adsorption ability. Results indicated that ceramics hydraulic conductivity have values 0.0024, and 0.0032 m/hr, respectively. The filtered water were tested for Â water quality parameters that the ceramic filters could remove, as an average percentages of removal, 99.9% Â Â to 3.26% by AKP1 and 100% to 64.67% Â by AKP2. The adsorption ability of the ceramics for solutes of seven heavy metals, Mn, Fe, Pb, Cd, Co, Cu and Zn, Â were measured. Results showed that most of the heavy metals ions were removed by the both types of filters that the removal varies between 98.18 and 100% of the initial concentration of each metal.Â The adsorption capacities of each filter to adsorb the heavy metals were computed according to Langmuir model and Freundlich models. The results showed The data were most fitted to Freundlich model. Â